Rediscovering the wisdom of the Corinthians: Paul, stoicism, and spiritual hierarchy - Brookins, Timothy (William B. Eerdmans Publishing Company, 2024)
"Timothy A. Brookins argues that Paul addresses a church conflict inspired by Stoicism in 1 Corinthians 1-4"--